Optimalisasi Peran Masjid Dalam Pendidikan Anak: Perspektif Makro Dan Mikro - Afiful Ikhwan (Tarbiyah Departement collaboration with AMCA, 2013)
The mosque as an instrument that can use to prostrate, also means it can use for social activities involving human dimension by making it as a central activity. Also relates to the potential mosque itself should be empowered with all the ability of the managers. In this case, it takes expertise (skills) are not only sufficient but must be fully implemented as the implementation of the propaganda bi ahsan al-'amal (make changes by mobilizing all abilities). With this kind of understanding, the mosque can be interpreted as an instrument or means of universal worship. Worship Not only mahdhoh (micro), but also worship ghayro mahdhah (macro). So, mosques back again in his role as the time of Prophet Muhammad saw- before that, as an educational centre that seeks to educate the religion of Islam and its values​​, to become one's way of life.